Influence of COVID-19 pandemic on psychosocial wellbeing of lecturers in rural campuses of selected South African universities - Newlin, Marongwe; Israel, Kariyana (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this paper was to explore the influence of COVID-19 pandemic on psychosocial wellbeing of rural university lecturers in South Africa. The study adopted a qualitative phenomenological design utilising snowball sampling technique to select 25 lecturers across five campuses of three different types of universities. Purposive sampling was adopted to choose the three faculties of the five rural campuses from the three participating higher education institutions (HEIs). Findings were classified under three themes namely emotional alienation, degenerating physical wellness and waning socioeconomic wellbeing. It emerged that lecturers were going through different psychological, emotional and social dilemmas that negatively affected their mental and physical wellbeing. These include mental strain due to e-resource under-provision, minimised teaching and learning efficacy as well as tech-related burnout. Ill-health due to lack of basic amenities, increased personal underdevelopment and increasing pressure from social adjustment demands also emerged among the psychosocial influences of the pandemic. The paper concludes that lecturers in both private and public HEIs are faced with a myriad of challenges amid the COVID-19 pandemic, and that lecturer stress impacts levels of lecturer efficacy on student learning. Recommendations made include the need by HEIs to set up dedicated counselling services for employees where there could vent and get help. Also, the onset of this pandemic should lead to rethinking of how lecturing should be envisaged going forward. The study is germane to provide a picture of some of the concerns regarding the wellbeing of lecturers upon which policy ought to be holistically entangled so as to promote socioeconomic development.